Learning through engagement: MOOCs as an emergent form of provision. Issue 2 (3rd May 2016) - Walji, Sukaina; Deacon, Andrew; Small, Janet; Czerniewicz, Laura
Abstract: Massive open online courses (MOOCs) are a new form of educational provision occupying a space between formal online courses and informal learning. Adopting measures used with formal online courses to assess the outcomes of MOOCs is often not informative because the context is very different. The particular affordances of MOOCs shaping learning environments comprise scale (in terms of numbers of students) and diversity (in terms of the types of students). As learning designers, we focus on understanding the particular tools and pedagogical affordances of the MOOC platform to support learner engagement. Drawing on research into learner engagement conducted in the broader field of online learning, we consider how learner engagement in a MOOC might be designed for by looking at three pedagogical aspects: teacher presence, social learning, and peer learning.